Pengaruh latihan box drill dan small sides games terhadap kemampuan passing pada pemain SSB HW Mandiangin - Ulfaizin, Muhammad Syifa; Rakhman, Arie; Mulhim, Muhammad (Universitas Hamzanwadi, 2024)
The purpose of this study is to determine the effect of the training methods of box drill and small side games on the passing ability of SSB HW Mandiangin players between the ages of 13 and 15. The players have not been able to pass properly, so frequent passing errors become a problem in playing soccer. The type of research used is experimental research with the design of